Bioefficacy of fluazifop-p-buty1 for weed control in soybean (Glycine max) - TIWARI, J P; KURCHANIA, S P; PARADKAR, N R (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during the rainy season (kharif) of 1990 and 1991 to study the bioefficacy of fluazifop-p-buty1 for controlling weed in soybean [Glycine max (L.) Morr.]. Three concentrations(0.125, 0.25 and 0.5 kg/ha) of fluazifop-p-buty1 were applied at post-emergence stage at 15 and 21 days after sowing. Fluazifop-p-buty1 at all the rates and times of application was effective in controlling barnyard grass [Echinochloa crus-galli (L.) P. Bcauv.], hairy crabgrass [Digitaria adseedens (H. B. & K.) Henr.]. wild sugarcane (Saccharum Spontaneum L.) and bermuda grass [Cynodon dactylon (L.) Pers.) but did not prove effective for the sedges and broad-leaf weeds. Fluazifop-p-buty1@ 0.125 kg/ha at 21 days after sowing could control the grassy weeds and increase the seed yield (2 124 kg/ha). Thus in soybean-weed ecosystem where sedges and broad-leafweeds are co-dominant. application of fluazifop-p-buty1 at 15 days after sowing and hand-weeding at 21 days after sowing is suitable for higher yield of soybean (2 296 kg/ha).